Israel and Hezbollah : A Cautious Stability - Bullock, Grant (Politics and economics of the Middle East., 2014)
Lebanon's Hezbollah is a Shiite Islamist militia, political party, social welfare organization, and U.S. State Department-designated terrorist organization. Its armed element receives support from Iran and Syria and possesses significant paramilitary and unconventional warfare capabilities. The 2006 war between Israel and Hezbollah has generated a vast amount of academic and military studies, including a number from the Strategic Studies Institute. Specifically, authors have tried to identify the new patterns of warfare through this conflict and sometimes have even called it the first illustra.